Health, illness, and use of care the impact of social factors - Kronenfeld, Jennie J. (Amsterdam ; New York : JAI, 2000)
This text explores the impact of social factors on health, illness and the use of care. Contributors examine a number of social factors including sex, gender and socio-economic status on the healthcare experience and focus on both patients within the care process and the providers of care. It also presents papers employing a variety of methodological approaches. In the range of illnesses discussed, the social factors under consideration, and the variety of methodological approaches, this volume represents the diversity within the field of medical sociology.
Includes bibliographical references.
Description based on print version record.
Keywords: Patients -- United States -- Social conditions; Health services accessibility -- United States; Women's Health Services -- United States; Delivery of Health Care -- United States; Health Behavior -- United States; Socioeconomic Factors -- United States; Health systems & services; Social issues & processes; Social Science -- Sociology -- General; Medical -- Health Care Delivery